Between History and Fiction: The Rhetoric of Memory in Daniel Riquelme’s Prose (1893-1911) (2014)
The article explores the tensions and relationships between fictional and historical discourses in the work of the Chilean writer Daniel Riquelme, specifically the uses and types of memory as critical dialectic between forgetting and remembering in his pr